Inconsistency of Regulations Causes Small Parking Revenue - Priskila, Rahel Eunike (Universitas Brawijaya, 2020)
Parking tax revenue in malang is small eventhough the potential is large. According to the Major of Malang, Sutiaji, said that parking tax revenues were far from their intended target. Many potential of Malang's parking tax are incorrect. There is a potential of more than IDR 100 billion, but the City Government only gets around IDR 7 billion to IDR 10 billion. Malang Corruptiob Watch also thinks that Malang City's parking revenue is not optimal and far from its potential. Parking revenue that is less than this target was also explained by the Head of Malang City's Regional Tax Service Agency, Ade Herawanto. Parking revenue that is far from this target is also supported by a summary of the 2018 APBD in Malang for only IDR 10 billion. The purpose of this study is to find informal factors that affect the small parking revenue received by Malang. Matters about the size of the tax revenue are usually analyzed by policy theory or implementation, but the author has discovered something new from the informal factor through a new institutionalism approach, namely the existence of unwritten rules of parking practices whiches is an inconsistency of Transportationn Departmenent regulations regarding parking practices. In this study, the author used a qualitative approach. Researchers use case studies as a research method.